DISASTER EMERGENCY TRAINING TO INCREASE MIGRANT CAPACITY IN SIDOARJO - Rofik, Ainul; Putra, Reza Hery Mahendra; Sahri, Moch.; Winoto, Priyo Mukti Pribadi; Bariyah, Khadijah Khairul (Community Service Journal of Indonesia, 2024)
Migrants seeking asylum in Indonesia are a vulnerable group who need attention and training regarding disaster emergencies. This is because Indonesia is a maritime country which geographically and geologically allows natural disasters to occur. Although aid supplies are very important in emergency situations, preventive measures and preparedness are also equally important so it is necessary to provide health services in the form of expertise in disaster emergencies for migrants. Disaster emergency management efforts are a system that cannot be divided and the quality of life of patients after a disaster injury depends on pre-hospital stage treatment. The aim of this activity is to increase understanding and empowerment by provide outreach and training for migrants living in Sidoarjo. Before counseling, a 10 minutes pre-test was conducted for the participants. followed by a counseling session, training and discussion session for approximately 60 minutes, and after that a post-test was carried out for 10 minutes. Next, the results of the pre-test and post-test are assessed and data processing and evaluation are carried out. The results of the Paired T-tests show a p-value of 0.00 so the sig value is <0.05 which indicates there is a significant difference regarding the pre-test and post-test data. This can be interpreted as an increase in insight, understanding, empowerment, as well as a change in attitude towards migrants after attending the counseling session. Community service activities regarding disaster emergencies for migrants living in Sidoarjo have had a significant impact in the form of increasing insight and empowerment regarding the topic of disaster emergencies.